Development of a Character Education Model in Schools - Agus Abdussalam; Aan Hasanah; Bambang Samsul Arifin (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to explore and analyze various approaches and strategies in developing character education models in schools. The method used is library research, by collecting and analyzing data from various relevant literature sources. This research provides in-depth insight into how schools can integrate character values into the curriculum and learning environment. Through this research, it is hoped that the development of an effective character education model involves steps such as identification of relevant character values, integration of character values in the curriculum, role models and real examples, active and reflective learning, involvement of parents and the community, as well as evaluation and feedback. This research also indicates that consistency and commitment from all school components is very important in building and strengthening character education. This research is expected to contribute to theoretical understanding of the importance of character education in forming students who are responsible, ethical and contribute positively to society